Determinants of maternity waiting home utilization among women who gave birth in public health facilities in the Gedeo Zone, southern Ethiopia: an unmatched case–control study - Tilahun, Dawit; Shaka, Mohammed Feyisso; Belay, Moges Mareg (Frontiers in Global Women's Health, 2023)
Background: Maternal mortality is still unacceptably high even though most of the causes of were preventable.One way of tackling this problem is establishing maternal waiting home close to the health facility. Even if the benefits of the maternal waiting home have been well documented, the determinants of its use were not well studied. This study aimed to identify determinants of maternal waiting for home utilization among women who gave birth in public health facilities of Gedeo zone, Southern Ethiopia.Methods: A facility-based unmatched case-control study was conducted from January to February, 2020, among129 cases and 257 controls.The data was entered into the Epi-Data version 3.1 and exported to the SPSS version 20 statistical package for analysis.Descriptive statistics including frequency,means, and standard deviations were computed. Association between variables was checked using logistic regression analysis and ORs with their 95% CI were used to determine the strength of association. P-value<0.05 was used as a cut of point to measure statistical significance.Result: A total of 378 respondents (126 cases and 252 controls) were successfully making the response rate 97.9%. The mean age of the participants was 27.4 (±5.6 SD) years which is 28.4 (± 5.5 SD) years for cases and 26.9 (±5.69 SD) years for controls. Women's educational status